2017
DOI: 10.1111/dme.13436
|View full text |Cite
|
Sign up to set email alerts
|

Bolusing frequency and amount impacts glucose control during hybrid closed‐loop

Abstract: AimTo compare bolus insulin delivery patterns during closed‐loop home studies in adults with suboptimally [HbA1c 58–86 mmol/mol (7.5%–10%)] and well‐controlled [58 mmol/mol (< 7.5%)] Type 1 diabetes.MethodsRetrospective analysis of daytime and night‐time insulin delivery during home use of closed‐loop over 4 weeks. Daytime and night‐time controller effort, defined as amount of insulin delivered by closed‐loop relative to usual basal insulin delivery, and daytime bolus effort, defined as total bolus insulin del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Third, we consciously enrolled a broad patient population for thisstudy,including (22). The frequency of premeal bolusing also is important, emphasizing the need for ongoing diabetes education and support with the closed-loop system (23). Others have commented that closed-loop insulin delivery may have unintended effects on dietary intake and proposed that education tooptimize healthyeating patterns be incorporated into closed-loop training (24).…”
Section: Discussionmentioning
confidence: 99%
“…Third, we consciously enrolled a broad patient population for thisstudy,including (22). The frequency of premeal bolusing also is important, emphasizing the need for ongoing diabetes education and support with the closed-loop system (23). Others have commented that closed-loop insulin delivery may have unintended effects on dietary intake and proposed that education tooptimize healthyeating patterns be incorporated into closed-loop training (24).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of daytime euglycemia is strongly linked to the time spent in Auto Mode, optimal ICRs, and proper patient behavior. Bally et al (41) recently reported that bolusing behavior and frequency during HCL use correlated positively with time spent in target glucose range.…”
Section: Time In Range Glucose Targetsmentioning
confidence: 99%
“…A total of 14 studies were included (Table 5 in the Supplementary Information): 11 trials, two analyses of trial data, and one real-world study [10,[72][73][74][75][76][77][78][79][80][81][82][83][84]. Four of the studies included participants under 18 years old, one included only participants over 60 years old, and two of the studies included pregnant women.…”
Section: Camaps Fxmentioning
confidence: 99%